2006
DOI: 10.1002/bdd.482
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic interaction of nelfinavir and methadone in intravenous drug users

Abstract: Although nelfinavir reduced the plasma concentrations of both R- and S-methadone, it seems to have no impact on the maintenance dose of methadone. A routine reduction of methadone dose is not recommended when coadministered with nelfinavir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
(22 reference statements)
2
14
0
Order By: Relevance
“…Several mechanisms discussed by the authors included nelfinavir being highly bound to AGP, and an inducer or inhibitor of both the CYP P450 enzyme system and P-gp. Similar results were found by Hsyu et al 100 and Marco et al 101 in studies of 14 and seven patients, respectively. Both recommended that a routine reduction of methadone dose was not necessary when administered with nelfinavir.…”
Section: Nelfinavirsupporting
confidence: 92%
See 1 more Smart Citation
“…Several mechanisms discussed by the authors included nelfinavir being highly bound to AGP, and an inducer or inhibitor of both the CYP P450 enzyme system and P-gp. Similar results were found by Hsyu et al 100 and Marco et al 101 in studies of 14 and seven patients, respectively. Both recommended that a routine reduction of methadone dose was not necessary when administered with nelfinavir.…”
Section: Nelfinavirsupporting
confidence: 92%
“…Suggested mechanisms include nelfinavir binding to AGP and both induction and inhibition of P-gp and the CYP P450 system. (78,(99)(100)(101) Nevirapine Decrease Six independent studies and case reports found withdrawal symptoms after nevirapine and methadone treatments. Nevirapine is a potent inducer of CYP P450 enzymes.…”
Section: Naloxonementioning
confidence: 98%
“…In the presence of ritonavir, which is a very potent inhibitor of CYP3A, any possible effects of methadone on CYP3 metabolism of atazanavir are most likely to be superimposed. Previous studies with, for example, nelfinavir have not shown any influence of methadone on the metabolism of HIV protease inhibitors [9].…”
Section: Resultsmentioning
confidence: 82%
“…In patients on daily methadone, nelfinavir 1250 mg twice daily reduced the AUC of oral RS-methadone by 38% (McCance-Katz et al, 2004), and the AUC of oral R- and S-methadone by 43 and 51%, respectively (Hsyu et al, 2006). This is essentially identical to the 40 and 49% reduction of single-dose oral methadone enantiomers in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Methadone-antiretroviral drug interactions are common, and are typically attributed to CYP3A4, although the actual mechanism(s) remain largely unknown (Bruce et al, 2006; Maas et al, 2006; Robertson et al, 2007). The HIV protease inhibitor nelfinavir decreases plasma concentrations of both S- and R-methadone (the active enantiomer) in half, yet there are generally no withdrawal symptoms or need for dose adjustment in patients on daily methadone (Hsyu et al, 2006; McCance-Katz et al, 2004), with some exception (Brown et al, 2006). Nelfinavir is a well-known inhibitor of CYP3A activity, yet the apparent paradox of nelfinavir induction of methadone elimination, despite CYP3A inhibition, has never been addressed.…”
Section: Introductionmentioning
confidence: 99%